RANCANG BANGUN SISTEM MONITORING KADAR BIOETANOL PADA ALAT PEMURNIAN BIOETANOL TERINTEGRASI CYBER-PHYSICAL SYSTEM - Pasaribu, Dimpos Fransiskus Xaverius; Nurussa’adah, n/a; Setyawati, Onny (Jurnal Mahasiswa TEUB, 2024)
Currently, the Indonesian government is promoting the development of renewable energy sources as an alternative to etroleum-based fuels. This effort is reflected in Presidential Regulation No. 40 of 2023, which governs policies on the provision of bioethanol as a biofuel. However, not all bioethanol can be used as fuel; only bioethanol with a concentration above 99%, known as fuelgrade, can be utilized. Due to this problem, there is a need to design and build a device capable of purifying regular bioethanol to achieve fuel-grade concentration, equipped with a monitoring system. This monitoring system is implemented to facilitate the testing and analysis of the purification process. The device uses the pervaporation method for purification, utilizing zeolite nanoparticle membranes as the purification medium. The device is equipped with an MQ3 ethanol sensor as the main component of the monitoring system. To enhance monitoring capabilities, the device is also integrated with a Cyber-Physical System. Thisintegration uses the ESP32 microcontroller to transmit data from the purification device to an Android application and an LCD monitor. This provides ease for researchers in directly monitoring the results of the purified bioethanol. From the research and analysis results, it was found that the Bioethanol Purification Monitoring System provided ethanol concentration readings with an average error of ±4% and an accuracy level of ±95%. The performance of the Cyber-Physical System built can transmit readingsfrom the MQ3 sensor to the LCD monitor both via cable and wirelessly using the Bluetooth protocol controlled by the ESP32. Data can be transmitted continuously over a long period without significant interference. The purification system built can purify ethanol from a 70% concentration to 99% with two purification cycles. The first purification cycle produced ethanol with an 84% concentration (a 14% increase), and the second cycle produced ethanol with a 99% concentration (a 15% increase). Keywords: Bioethanol, Monitoring System, CyberPhysical System, MQ3, ESP32